Model of Supervision Based on Primary School Teacher Professional Competency in Tematic Learning in Curriculum 2013 - Hartono, Meilani (Journal of Education Reseach and Evaluation, 2017)
This study aims to find the Supervision Model Based on Primary Teacher Professional Competence which effective on integrated learning. This study use research and development with qualitative approach which will be carried out in the Palmerah, West Jakarta. The techniques used to collect data are interviews, questionnaires, observation and documentation. Data v alidity is tested withÂ credibility, transferability, dependability,Â andÂ comfortability. The model developed will be validated using the Delphi technique. The result of this research is the discovery of the model and device-based supervision model of professional competence of primary teachers in integrated learning. The long-term goal of this research is to improve the teachersâ competence and the supervision quality for primary teachers in integrated learning